2015
DOI: 10.1111/opo.12200
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and comparison of clinical techniques for anterior chamber angle assessment

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Coherence Tomography (AS-OCT) and determine the agreement between these techniques within a community optometry setting. Permanent repository link MethodsGonioscopy, van Herick method and AS-OCT imaging were performed by an optometrist on two occasions, one month apart, on 80 subjects aged over 40 years recruited from community optometry practices. Anterior segment images were captured with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 29 publications
1
25
1
1
Order By: Relevance
“…This is consistent with the reported literature [7, 21]. Although gonioscopy has traditionally been the gold standard for grading ACAs, given the intraobserver (intervisit) agreements found in our study and those published by Campbell et al [10], it is not clear that it is a more reliable representation of the true angle status as open or narrow when compared to ASOCT, which may be the result of examiner technique or dynamic anatomic variation in the individual.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This is consistent with the reported literature [7, 21]. Although gonioscopy has traditionally been the gold standard for grading ACAs, given the intraobserver (intervisit) agreements found in our study and those published by Campbell et al [10], it is not clear that it is a more reliable representation of the true angle status as open or narrow when compared to ASOCT, which may be the result of examiner technique or dynamic anatomic variation in the individual.…”
Section: Discussionsupporting
confidence: 87%
“…Intraobserver (intervisit) kappas were 0.57 and 0.83 for readers 1 and 2, respectively, in our study, which was better than previously published results (kappa = 0.47) using the spectral domain Topcon OCT (Topcon Europe Medical BV, Netherlands) in the anterior segment mode (840 nm wavelength) [10]. …”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The repeatability of gonioscopy was fair (κ = 0.29), while that of AS-OCT (κ = 0.47) was better. 21 The identification of the scleral spur location represents an important anatomical landmark for the evaluation of angle closure. Sakata et al observed that the scleral spur location could not be detected in approximately 30% of the anterior chamber angle images obtained with the Visante AS-OCT.…”
Section: Published Resultsmentioning
confidence: 99%